Sun Yat Sen and the Chinese republic - Linebarger, Paul Myron (The century Co., 1925)
Contents: During the years 1901 to 1907, while the author was a circuit judge in the Philippines, he had in his service a very excellent Cantonese cook named Ah Po, whose attendance, during the sea voy ages from court to court, was indeed appreciated, especially during the trying period of cholera epidemics, when the preparation of the food was a vital matter This sentiment of appreciation developed into real gratitude when, on the occa sion of a certain ship adventure, Ah Po saved the authors life. Encouraged by this gratitude, Ah Po eventu ally confided that he was one of Sun Yat Sens DaretoDies and that he wanted a substantial loan and leave of absence to return to China. These requests being granted, faithful Ah Po went his way, and only after long weeks overdue did he return, more dead than alive. The Impe rialists had caught him, put him on the torture rack, and finally thrown him out for dead. This brutality, together with Ah Pos direct informa the great Reformer, for so insurmountable was Suns modesty that he had given out no detailed information concerning himself, and particularly of his early life